2021
DOI: 10.32457/ijmss.v8i1.655
|View full text |Cite
|
Sign up to set email alerts
|

Síntomas de Ansiedad y Depresión en Personal de Salud que Trabaja con Enfermos de COVID-19

Abstract: Public health personnel facing COVID-19 are exposed to multiple risks including psychological disorders. The goal of this study was to determine the presence of symptoms associated with anxiety and depression in health personnel working with COVID-19 patients. A descriptive cross-sectional study involving 61 health care professionals and technicians was conducted, working directly with COVID-19 patients, who were consulted about the presence of symptoms associated with depression and anxiety, their main concer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
(11 reference statements)
0
2
0
3
Order By: Relevance
“…The reported symptoms included increased appetite, feeling short of breath and sweating, with headaches being the most frequently reported (32% and 33%). 19 In the context of Colombia, Restrepo-Martínez et al conducted a study in the city of Medellin between March and May 2020. The study indicated that one out of five respondents displayed symptoms of anxiety, such as restlessness nervousness, worrying over various matters, difficulty relaxing and fear 7 -symptoms akin to those identified in this study.…”
Section: Symptoms Of Anxietymentioning
confidence: 99%
“…The reported symptoms included increased appetite, feeling short of breath and sweating, with headaches being the most frequently reported (32% and 33%). 19 In the context of Colombia, Restrepo-Martínez et al conducted a study in the city of Medellin between March and May 2020. The study indicated that one out of five respondents displayed symptoms of anxiety, such as restlessness nervousness, worrying over various matters, difficulty relaxing and fear 7 -symptoms akin to those identified in this study.…”
Section: Symptoms Of Anxietymentioning
confidence: 99%
“…3,9 In China, more than 1000 people were evaluated in several cities, and it was shown that 16.5% presented symptoms of stress and 28.8% symptoms of anxiety. 10 In the same context, Peru is no stranger to this problem since a study conducted in Chota on anxiety in times of social isolation by COVID-19, showed that 43% of participants had anxiety, of which 20.9% had mild anxiety, 13.4% had moderate anxiety and 9% had severe anxiety. 11 Self-medication is a non-responsible act and leads to the inappropriate use of medications, causing low effectiveness and insecurity in treatments, damage to health and patient dissatisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…En general, podemos mencionar que las profesionales, las enfermeras y quienes trabajan directamente con casos sospechosos o confirmados de COVID-19 tienen mayor riesgo de padecer problemas de salud mental. Si se desea contener adecuadamente la pandemia, se debe propiciar el cuidado de la salud mental del personal sanitario (Miranda y Murguía, 2021).…”
Section: Alta Claridad Emocionalunclassified